2020
DOI: 10.1002/brb3.1777
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen improved the regeneration of axons after subcortical axon injury via regulation of PI3K/Akt/CDK5/Tau pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the transmembrane receptor protein tyrosine kinase signaling pathway was significantly enriched, indicating that RTK signaling may be the primary upstream pathway used by the CH02 peptide. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified enrichment in pathways, most of which are involved in regulating axon outgrowth or regeneration, including AMPK 41 and MAPK signaling 14 , 45 - 47 , regulation of actin cytoskeleton 48 , 49 , and calcium 3 , 50 , mammalian target of rapamycin (mTOR) 6 , 51 - 54 , VEGF 55 - 58 , and PI3K-Akt signaling (Figure 6 B) 8 , 59 , 60 . Of note, several of these signaling pathways are directly or indirectly regulated by FGFRs or other RTK signals 22 , 61 - 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the transmembrane receptor protein tyrosine kinase signaling pathway was significantly enriched, indicating that RTK signaling may be the primary upstream pathway used by the CH02 peptide. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified enrichment in pathways, most of which are involved in regulating axon outgrowth or regeneration, including AMPK 41 and MAPK signaling 14 , 45 - 47 , regulation of actin cytoskeleton 48 , 49 , and calcium 3 , 50 , mammalian target of rapamycin (mTOR) 6 , 51 - 54 , VEGF 55 - 58 , and PI3K-Akt signaling (Figure 6 B) 8 , 59 , 60 . Of note, several of these signaling pathways are directly or indirectly regulated by FGFRs or other RTK signals 22 , 61 - 65 .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the kinase phosphorylating tau in a GAS5-dependent manner is not GSK3α/β. Others have shown that AKT and CDK5 47 or MARK 48 mediate tau phosphorylation. Future studies utilizing kinase assays, mutations of phospho sites on tau will be undertaken by us to identify the GAS5-dependent kinase phosphorylating tau in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…ERP30 is an ER among membrane receptors ( 19 ). Estrogen activates the PI3K-Akt signaling pathway after binding to the ER ( 22 , 23 ). Furthermore, the PI3K-Akt signaling pathway is one of the pathways that promote cell proliferation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%